Analisis Penerapan Penggunaan Alat Pelindung Diri (APD) - Solehudin Solehudin; Sancka Stella; Dwi Mahbubiyah Fi Qolbi; Ahmad Rizal; Lannasari Lannasari; Irma Herliana; Emi Yuliza; Rina Aprina; Eka Rokhmiati; Indri Sarwili; Nurul Ainul Shifa (Pusat riset dan Inovasi Nasional, 2024)
The incidence of infection is considered a serious problem that threatens the health and safety of patients and health workers globally. Nosocomial infections are infections that occur in hospitals and attack sufferers who are in the healing process. Personal protective equipment (PPE) is equipment that workers must use when carrying out work that poses a risk of compromising safety and health. The aim of this research is to determine the implementation of the use of personal protective equipment (PPE) in room D of one of the Bogor city hospitals. The type of research is in the form of a case study of nursing management station nurse practice which was carried out October 16 – November 10 2023. Data collection tools used observation and checklist sheets. The results of research on the types of Personal Protective Equipment (PPE) used in room D consist of handscoone, mask, apron, haircap and shoes. The personal protective equipment (PPE) used in room D was found to be incomplete. The implementation of the use of Personal Protective Equipment (PPE) used in room D was found to be poor, because of the 5 nurses only 3 nurses applied it well (70%), the rest were not good (30%). And in conclusion, implementing the use of Personal Protective Equipment (PPE) is very important for health workers, especially nurses, when carrying out medical procedures to avoid nosocomial infections..